Mites of the genera Pulaeus and Lupaeus (Acari: Prostigmata: Cunaxidae) of Crimea, Ukraine - Sergeyenko, Alexey L. (Zootaxa, 2011)
Four new mite species from the Crimean Peninsula (Ukraine), viz. Pulaeus leonidi sp. nov., P. maslovi sp. nov., P. semistriatus sp. nov. and Lupaeus valentinae sp. nov. are described and illustrated. The female and male of Pulaeus krama (Chaudhri, 1977) are redescribed based on Crimean specimens. Pulaeus longignathos Bu & Li, 1987 syn. nov. and P. chongqingensis Bu & Li, 1987 syn. nov. are considered as the male and the female of P. krama, respectively. P. krama is recorded from Crimea for the first time. New nomenclatural combinations are proposed. Keys to species of the Pulaeus and Lupaeus of the Crimea are provided.